LAND RELATIONS REFORM IN UZBEKISTAN:LEGAL FOUNDATIONS AND ADVANTAGES OF THE PRIVATIZATION OF NON-AGRICULTURAL LAND (International journal of artificial intelligence, 2026)
The large-scale transformations implemented in the field of land legislation in Uzbekistan are widely recognized as one of the most significant reforms in the country’s modern history. In the context of rapid globalization, accelerating the privatization of non-agricultural land plots has become a matter of particular relevance for achieving sustainable and inclusive economic growth, forming a healthy competitive environment, intensifying investment flows, strengthening the confidence of the business community, and integrating land resources into full-fledged economic circulation.Previously, land was considered exclusively state property and was granted to individuals and legal entities solely on the basis of rights of use, possession, or lease. At present, however, legal opportunities have been created to formalize non-agricultural land as private property.The regulatory legal acts adopted in recent years have established the legal foundations for the privatization of non-agricultural land and may be regarded as a truly transformative step in the development of land relations in Uzbekistan.